Masculinity, resources, and retention in care: South African men's behaviors and experiences while engaged in TB care and treatment. (February 2021) - Daniels, Joseph; Medina-Marino, Andrew; Glockner, Katherine; Grew, Emily; Ngcelwane, Nondumiso; Kipp, Aaron
Abstract: Rationale: Globally, the prevalence of tuberculosis (TB) disease is significantly higher among men compared to women. This is compounded by men's poorer uptake of TB testing and treatment, and worse outcomes for smear conversion and successful treatment completion compared to women; in South Africa specifically, TB accounts for a large portion of sex-specific life expectancy differences. Objective: To understand men's unique barriers to accessing care and their needs while engaged in TB treatment, we conducted a qualitative study with men currently in or who recently completed TB treatment to understand how social norms for masculinity influence resource access and health behaviors, and in turn affect their engagement in care. Methods: We interviewed 31 men using a semi-structured protocol, with domains including: social network composition and support; TB illness; and testing, treatment, and clinical care experiences. Interviews were analyzed using a constant comparison approach to identify resources and how these are exchanged within men's social networks for TB care. Results: We found that men's prioritizing of work ensured food security and maintenance of masculinity norms, but delayed seeking and engagement in care. Once in treatment, men found it difficult both to negotiate clinic hours and work schedules and to navigate clinic environments without being labeled as weak. To mitigate individual resource gaps and losses, men typically accessed women family members who provided key resources (e.g., food, money, and emotional encouragement). Masculine identification with fatherhood was a key motivator to remain engaged in TB care and treatment. Loss from care was facilitated by isolation and limited access to social network resources. Conclusion: To improve men's engagement in care and successful treatment outcomes, interventions that leverage their social networks and build upon existing resources should be strongly considered. Highlights: A catch-22 involving resources and manhood norms compromises men's TB treatment. Women's mitigation of men's resource gaps impacts men's sense of manhood. Men recognize that masculine social norms "is what kills us.". Barriers that seem to be gender-neutral, may have gender-specific effects on health behaviors. Fatherhood is a key motivator for men to engage in and complete TB treatment.